Luminescent properties of Mg3Ca3(PO4)4: Eu2+ blue-emitting phosphor for white light emitting diodes - Li, Y.; Deng, D.; Wang, Q.; Li, G.; Hua, Y.; Jia, Guohua; Huang, L.; Zhao, S.; Wang, H.; Li, C.; Xu, S. (2012)
A blue-emitting phosphor, Eu 2-activated Mg 3Ca 3(PO 4) 4 phosphor was synthesized by conventional solid-state reaction. X-ray powder diffraction (XRD) analysis confirmed the phase formation. Photoluminescence (PL) results showed that Mg 3Ca 3(PO 4) 4: Eu 2 could be efficiently excited by UVvisible light from 250 to 430 nm, which matched well with the emission wavelengths of near-UV and UV LED chips. The effects of the doped-Eu 2 concentration in Mg 3Ca 3(PO 4) 4: Eu 2 on the PL were also investigated. The result reveals that Mg 3Ca 3(PO 4) 4: Eu 2 is a potential blue-emitting phosphor for white LEDs. © 2011 Elsevier B.V. All rights reserved.